2020
DOI: 10.1186/s12886-020-01535-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of the removal of posterior segment metallic intraocular foreign bodies

Abstract: Background: Posterior segment metallic intraocular foreign bodies (IOFBs) are a leading cause of visual morbidity and blindness, especially among young and middle-aged working populations. Here, we aimed to evaluate the surgical outcomes of the removal of such IOFBs that result from injuries. Methods: In this retrospective study, 39 patients injured by metallic posterior segment IOFBs and who underwent primary repair procedures, vitrectomies, and IOFBs removal with or without procedures for traumatic cataract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Young men are more exposed to eye injuries due to the fact that they carry out more risky activities in this regard. The most common factors associated with the production of eye injuries were not wearing goggles and metal hammering [ 1 , 6 , 9 , 14 , 15 , 16 , 18 , 19 , 20 , 22 , 27 , 28 ]. In our case series, none of the subjects wore goggles, which is why we strongly support their crucial role in preventing eye damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Young men are more exposed to eye injuries due to the fact that they carry out more risky activities in this regard. The most common factors associated with the production of eye injuries were not wearing goggles and metal hammering [ 1 , 6 , 9 , 14 , 15 , 16 , 18 , 19 , 20 , 22 , 27 , 28 ]. In our case series, none of the subjects wore goggles, which is why we strongly support their crucial role in preventing eye damage.…”
Section: Discussionmentioning
confidence: 99%
“…Initial poor BCVA was correlated with a poor prognosis throughout our study ( p = 0.018). Previous research indicated that poor BCVA at presentation is a major risk factor for poor visual outcome, mainly because it reflects a higher degree of ocular damage at presentation [ 13 , 14 , 15 , 22 , 26 ]. In contrast, some authors did not find initial BCVA to be correlated with a poor visual prognosis, mentioning that vitreous hemorrhage or traumatic cataract, which can significantly affect initial BCVA, can be successfully resolved by surgery without impacting final BCVA [ 9 , 20 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a previous report, 6/11 eyes with intraocular cilia were caused by flips of iron wire [ 6 , 7 ]. Intraocular foreign bodies in the posterior segment present more serious prognoses [ 8 , 9 ]. As a type of autogenic biological foreign body, the eyes’ reaction to cilium varies unpredictably.…”
Section: Discussionmentioning
confidence: 99%